CONSISTENCY OF PLANNING AND BUDGETING IN EDUCATION: THE CASE IN PONTIANAK CITY - Kharisma, Bayu; Remi, Sutyastie S.; Ario, Bugi; Suhayli, Cecep (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
Human resource is one of key elements in national or regional development and one way to improve the quality of human resource is through education as higher education means better human resource in terms of quality. Education is one of priority programs in Pontianak city and it is obvious that their government has a plan to enhance their human resource quality through education as it is stated in their long-term and medium-term development plans. Hence, this study aims to identify inconsistency trends between planning and budgeting in education-specific programs and activities in Pontianak city’s government in 2019 using quantitative methods through data collection. Consistency analysis is carried out by evaluating several related documents like RPJPD 2005-2025, RPJMD 2015-2019, RKPD 2019, Renstra 2015-2019, Renja 2019, and DPA 2019. The result of the analysis shows that the planning and budgeting documents in education-specific programs and activities in Pontianak city are not fully consistent.